Picroside II Could Protect The Cerebral Ischemic Injury by Reducing The Content of Free Radical and Enhancing The Activity of Antioxidase in Rats - Yang, Guangwen; Zhang, Rui; Li, Xiaodan (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The aim is to optimize the anti-oxidation and the drug dose and medication time of picroside II by orthogonal test in cerebral ischemia in rats. The forebrain ischemia models were established by bilateral common carotid artery occlusion (BCCAO) methods. The successful models were randomly grouped according to orthogonal experimental design and injected picroside II intraperitonenally with different dose at different ischemic time for treatment. The contents of malondialdehyde (MDA), nitric oxide (NO) and hydrogenperoxide (H2O2) in brain tissue were respectively determined by thiobarbituric acid assay, nitratase reduase assay and chemiluminescence immunoassay. The activities of superoxide dismutase (SOD), glutathione peroxidase (GSHPx) and catalase (CAT) in brain tissue were respectively determined by xanthinoxidase assay, chemical colorimetry and chemiluminescence immunoassay. The results indicated that the best therapeutic time window and dose of picroside II in cerebral ischemic reperfusion injury was (1) ischemia 1.5h with 10mg/kg, 1.5h with 20mg/kg and 1.5h with 20mgkg body weight according to the contents of MDA, NO and H2O2 in brain tissue; (2) ischemia 1.5h with 20mg/kg, 2.0h with 20mg/kg and 1.5h with 10mg/kg body weight according to the activities of SOD, GSHPx and CAT in brain tissue. From the principle of lowest therapeutic dose with longest time window, the optimized therapeutic dose and time window is injecting picroside II intraperitonenally with 10-20mg/kg at 1.5-2.0h after cerebral ischemic injury.